Vanadium dioxide composite electrode material and preparation method and application thereof
By directly synthesizing and modifying vanadium dioxide composite electrode materials from vanadium leaching liquid and building a three-dimensional conductive network with carbon nanotubes, the performance problems caused by alkali metal lithium and sodium batteries due to dendrite and unstable SEI film are solved, and a higher performance problem has been achieved. Stability and reaction performance.
Patent Information
- Application Number
- CN202411557419.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
Alkaline metal lithium and sodium batteries are affected by dendrite formation and unstable SEI films, which have low efficiency, large capacity loss, short cycle life and serious safety hazards.
By directly synthesizing vanadium dioxide composite electrode material from vanadium leaching liquid, modifying it with mercaptosilane coupling agent and silver source, combining carbon nanotubes to build a three-dimensional conductive network to form a Vanadium dioxide composite film modified with Ag element.
It improves the stability and reaction kinetics of the electrode, enhances the electronic conductivity and reversible capacity, extends the cycle life of the battery, and reduces safety risks.
Smart Images

Figure HDA0005116902480000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a vanadium dioxide composite electrode material and a preparation method and application thereof. Background Art
[0002] Alkali metal batteries have the advantages of abundant reserves, low cost, high output voltage, strong adaptability, environmental friendliness and pollution-free, wide operating temperature range, fast charge and discharge, and high energy density. However, they still face many problems in practical application. At present, negative electrode materials represented by alkali metal lithium and sodium are highly reactive. Due to thermodynamic instability, they will spontaneously generate unstable solid electrolyte interface (SEI) membranes when in contact with electrolytes. Uncontrollable dendrite growth and unlimited volume expansion will occur in the later cycle process, resulting in low coulombic efficiency, capacity loss, short cycle life, and serious safety hazards for alkali metal batteries, which brings resistance to the practical application of alkali metal batteries.
[0003] The key to stabilizing alkali metal batteries, especially lithium and sodium metal negative electrode materials, is to enhance the thermodynamic stability and reaction kinetics of the negative electrode by modifying and regulating the physicochemical properties of the main material. At present, carbon materials have low mass density and are the most promising lightweight main materials. The structure and morphology, defects, microstructure and functional groups of pure carbon materials will affect the deposition and growth of alkali metals. Vanadium dioxide is a phase change material. When its phase change occurs, its crystal structure changes from monoclinic phase to tetragonal rutile phase, and its resistivity changes by more than 3 orders of magnitude, from a semiconductor before the phase change to a metal. Vanadium-based transition metal oxides have rich structures due to their different atomic configurations and multiple vanadium valence states, providing superior lithium storage capacity. In recent years, they have been used in smart glass, optical storage, laser radiation protection film, lithium battery electrodes, etc.
[0004] At present, the application and promotion of vanadium dioxide in electrodes is relatively rare due to the instability of its valence state. At the same time, most methods for preparing vanadium dioxide are to synthesize vanadium pentoxide and vanadium trioxide through solid-phase reaction, which is a complicated process. This technology proposes to directly synthesize vanadium dioxide from industrial raw materials - vanadium leaching solution, without the need for intermediate synthesis of vanadium pentoxide and vanadium trioxide and then reacting again. At the same time, the vanadium dioxide composite electrode material produced by this process can solve the problem that the battery performance of lithium / sodium batteries is seriously affected by the formation of dendrites and the formation of unstable SEI film. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a vanadium dioxide composite electrode material and a preparation method and application thereof. The vanadium dioxide composite electrode material is used as a negative electrode material of a battery and has excellent stability and reaction kinetics.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a vanadium dioxide composite electrode material, comprising the following steps:
[0008] (1) reacting the vanadium leaching solution with a reducing agent at a pH of 2 to 6, mixing the obtained tetravalent vanadium solution with a precipitant and causing a precipitation reaction to obtain a vanadium dioxide precursor suspension;
[0009] (2) mixing a silane coupling agent with a mercapto group with a vanadium dioxide precursor suspension and reacting the mixture to obtain an intermediate; subjecting the silver source to a chelating reaction with the intermediate and, under the action of a strong reducing agent, obtaining a vanadium dioxide precursor modified with Ag;
[0010] (3) mixing a vanadium dioxide precursor modified with Ag, a solvent and carbon nanotubes to obtain a vanadium dioxide precursor composite slurry;
[0011] (4) coating the vanadium dioxide precursor composite slurry on the surface of the substrate and calcining it to obtain a vanadium dioxide composite electrode material.
[0012] Preferably, the reducing agent is selected from oxalic acid.
[0013] Preferably, the molar ratio of the reducing agent to the vanadium ions in the vanadium leaching solution is 1:(1-2).
[0014] Preferably, the precipitant is selected from any one or more of urea, ammonia water or sodium hydroxide.
[0015] Preferably, the molar ratio of the precipitant to the vanadium ions in the vanadium leaching solution is (2-10):1.
[0016] Preferably, the pH is 2 to 6 and is regulated by concentrated sulfuric acid.
[0017] Preferably, the reaction temperature in step (1) is 80-100° C. and the reaction time is 1.0-3.0 h.
[0018] Preferably, the ion exchange is carried out at a temperature of 95 to 100° C. and for a time of 1.0 to 5.0 h.
[0019] Preferably, the silane coupling agent having a mercapto group is 3-mercaptopropyltriethoxysilane.
[0020] The silane coupling agent with mercapto groups accounts for 1-2% of the mass of the vanadium dioxide precursor suspension.
[0021] The silver source is selected from silver nitrate; the silver nitrate is added in the form of a solution, the concentration of the silver nitrate solution is 1-2.5 mol / L, and the mass of the silver source accounts for 0.5-1.5% of the mass of the vanadium dioxide precursor suspension.
[0022] Preferably, the strong reducing agent is selected from sodium borohydride.
[0023] Preferably, the molar ratio of the strong reducing agent to the silver ions in the silver source is 1:1 to 2:1.
[0024] Preferably, the reaction temperature of the silane coupling agent with a mercapto group and the vanadium dioxide precursor suspension is 10 to 30° C. and the reaction time is 16 to 24 hours.
[0025] Preferably, the solvent is selected from ethylene glycol, glycerol and polyvinyl pyrrolidone.
[0026] Preferably, the mass ratio of polyvinyl pyrrolidone, ethylene glycol and glycerol is 1:10:10 to 1:4:4.
[0027] Preferably, the carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0028] Preferably, the substrate is selected from copper sheets.
[0029] Preferably, the deposited vanadium dioxide precursor modified with Ag accounts for 8-20% of the total mass of the solution; the total mass of the solution is the total mass of the vanadium dioxide precursor modified with Ag, the solvent and the carbon nanotubes.
[0030] Preferably, the concentration of the carbon nanotubes is 0.5-1 mol / L.
[0031] Preferably, the mixing temperature in step (3) is 10-30° C. and the mixing time is 0.7-3 h; and an ultrasonic step is further included after the mixing.
[0032] Preferably, the calcination temperature is 500-600° C. and the calcination time is 1-3 hours.
[0033] Preferably, the calcination is carried out in an inert atmosphere.
[0034] In a second aspect, the present invention provides a vanadium dioxide composite electrode material prepared according to the above preparation method, which comprises a substrate and a vanadium dioxide composite film supported on the substrate;
[0035] The vanadium dioxide composite film is constructed by VO2 deposited with Ag single substance and carbon nanotubes.
[0036] Preferably, the vanadium dioxide composite film has a thickness of 50 to 200 μm.
[0037] In a third aspect, the present invention provides a secondary battery, wherein the negative electrode material of the secondary battery is the vanadium dioxide composite electrode material involved in the above technical solution.
[0038] Preferably, the secondary battery comprises a lithium ion battery or a sodium ion battery.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention provides a method for preparing a vanadium dioxide composite electrode material. The method uses vanadium leaching solution as a raw material. Compared with the prior art, the method starts from industrial raw materials and prepares the vanadium dioxide composite electrode material in situ. It does not need to generate intermediate products such as metavanadate and vanadium pentoxide for direct synthesis. It has the advantages of simplifying the process route and reducing the process cost. In addition, the composite product has better electronic conductivity, optimal reversible capacity and good kinetic reaction than traditional electrode materials. The present invention reacts the vanadium leaching solution with a reducing agent under the condition of pH 2 to 6, and ion exchanges the obtained tetravalent vanadium mixture with a precipitant to obtain vanadium dioxide precursor particles, and then grafts a silane coupling agent with a mercapto group to the surface of the vanadium dioxide precursor through a coupling reaction, and chelates silver ions with the help of the mercapto group. After reduction, the silver element is deposited on the surface of the vanadium dioxide precursor particles. Then, the composite slurry of the vanadium dioxide precursor and carbon nanotubes is coated on the surface of the substrate and calcined to obtain the vanadium dioxide composite electrode material.
[0041] In the present invention, the vanadium dioxide composite electrode material prepared by the above preparation method includes a substrate and a vanadium dioxide composite film loaded on the substrate, wherein the vanadium dioxide composite film is constructed by VO2 (referred to as "VO2-Ag") deposited with Ag single substance and carbon nanotubes. In the present invention, the vanadium dioxide modified by nano-Ag single substance has the quantum effect, small-scale effect and surface effect possessed by nanomaterials, and also has the ability to move freely, penetrating power and super activity. At the same time, as a relatively cheap metal among precious metals, it has unique electronic properties, optical properties, mechanical properties and catalytic properties, which can enhance the electronic conductivity of the electrode. Furthermore, the three-dimensional conductive network constructed by carbon nanotubes helps to overcome the dynamic constraints of the battery during discharge, increase the intercalation depth of lithium and sodium ions and reduce the concentration difference of lithium and sodium ions on the surface of the particles, so that the composite electrode material exhibits the best reversible capacity and good kinetic reaction, and can also effectively prevent the agglomeration of VO2-Ag particles, and support sufficient space for the expansion of the matrix during the reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of vanadium dioxide composite electrode material;
[0043] Among them, 1 is a substrate, 2 is vanadium dioxide particles, 3 is nanosilver grafted on the surface of vanadium dioxide, and 4 is a carbon nanotube. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Alkali metal batteries such as lithium / sodium are widely used, but there are large technical barriers. Due to thermodynamic instability, unstable SEI films will spontaneously form when in contact with electrolytes, and uncontrollable dendrite growth and unlimited volume expansion will occur in the later cycle process, resulting in low coulombic efficiency, large capacity loss, short cycle life, and serious safety hazards of alkali metal batteries. Based on this, the present invention provides a method for preparing a vanadium dioxide composite electrode material, comprising the following steps:
[0046] (1) reacting the vanadium leaching solution with a reducing agent at a pH of 2 to 6, mixing the obtained tetravalent vanadium solution with a precipitant and causing a precipitation reaction to obtain a vanadium dioxide precursor suspension;
[0047] (2) mixing a silane coupling agent with a mercapto group with a vanadium dioxide precursor suspension and reacting the mixture to obtain an intermediate; subjecting the silver source to a chelating reaction with the intermediate and, under the action of a strong reducing agent, obtaining a vanadium dioxide precursor modified with Ag;
[0048] (3) mixing a vanadium dioxide precursor modified with Ag, a solvent and carbon nanotubes to obtain a vanadium dioxide precursor composite slurry;
[0049] (4) coating the vanadium dioxide precursor composite slurry on the surface of the substrate and calcining it to obtain a vanadium dioxide composite electrode material.
[0050] According to the present invention, firstly, the vanadium leaching solution is reacted with a reducing agent at a pH of 2 to 6, and the obtained tetravalent vanadium solution is mixed with a precipitant to undergo a precipitation reaction to obtain a vanadium dioxide precursor suspension.
[0051] In the present invention, the vanadium leaching solution is an industrial raw material taken from a vanadium product factory, and its main component is sodium vanadate. The present invention preferably reacts the vanadium leaching solution with a reducing agent under the condition of pH 2-6, preferably 3-4, to obtain a tetravalent vanadium solution. Wherein, the reducing agent is selected from oxalic acid, which can reduce the vanadium ions in the vanadium leaching solution to tetravalent vanadium; the molar ratio of the reducing agent to the vanadium ions in the vanadium leaching solution is 1: (1-2), preferably 1: (1-1.5), and more preferably 1: 1. The temperature of the reaction is 80-100°C, preferably 85-90°C; the reaction time is generally based on the color of the solution changing from orange-red to blue-black. According to experiments, the time is generally determined to be 1.5-2.5h, preferably 2.0-2.5h. It should be noted that the condition of pH 3-4 can make the subsequent tetravalent vanadium solution stable. Since the present invention prepares a vanadium dioxide composite electrode material, in order to avoid the introduction of other ions to cause corrosion to the electrode and other adverse effects, the present invention preferably uses concentrated sulfuric acid to adjust the pH to 2-6.
[0052] Then, according to the present invention, the obtained tetravalent vanadium solution is mixed with a precipitant and a precipitation reaction is carried out to perform ion exchange to obtain a vanadium dioxide precursor suspension. Wherein, the precipitant is selected from any one or more of urea, ammonia water or sodium hydroxide, and the molar ratio of the precipitant to the vanadium ions in the vanadium leaching solution is (2-10):1, preferably (3-5):1. The temperature of the precipitation reaction is 95-100°C, preferably 98-100°C; the time is 1.0-5.0h, preferably 1.5-2.5h, and the ion exchange is preferably carried out under stirring conditions. In this process, the tetravalent vanadium solution and the precipitant undergo a precipitation reaction to generate a solid intermediate product. It should be noted that in the present invention, the precipitation reaction time cannot be too short, otherwise the reaction will be incomplete, and it cannot be too long, otherwise the crystal form of the generated vanadium dioxide precursor will be non-target crystal form.
[0053] In some embodiments of the present invention, a certain amount of vanadium leaching solution (main component sodium vanadium sulfate) is preferably placed in a three-necked flask, wherein the concentration of vanadium ions is 40-50 g / L, concentrated sulfuric acid is used to adjust the solution pH to 2-6, and after heating to 80-100° C., a certain amount of reducing agent is added, and the molar ratio of the reducing agent to the vanadium ions is 1: (1-2). After insulation for 1.0-3.05 hours, the color of the solution changes from orange-red to blue-black to form a solution A, and a certain amount of precipitant is added to the solution A, and the molar ratio of the precipitant to the vanadium ions is (2-10): 1, and then heated to 95-100° C. and stirred for 1-5 hours to form a suspension B with a precipitate (i.e., a vanadium dioxide precursor).
[0054] Then, according to the present invention, a silane coupling agent with a mercapto group is mixed with a suspension B of a vanadium dioxide precursor and reacted to obtain an intermediate; a silver source is subjected to a chelating reaction with the intermediate, and then, under the action of a strong reducing agent, a vanadium dioxide precursor modified with Ag is obtained.
[0055] First, a silane coupling agent with a mercapto group is mixed and reacted with a suspension B of a vanadium dioxide precursor to obtain an intermediate. The silane coupling agent with a mercapto group is 3-mercaptopropyltriethoxysilane, and the mass fraction of the silane coupling agent with a mercapto group in the suspension B is 1 to 2%, preferably 1.2 to 1.5%. The above mixing and reaction are preferably carried out under stirring conditions. In the present invention, the reaction temperature is room temperature, specifically 10 to 30°C, preferably 15 to 25°C; the time is 16 to 24 hours, preferably 18 to 22 hours. In this process, the silicon group in the silane coupling agent with a mercapto group undergoes a coupling reaction with the hydroxyl group in the vanadium dioxide precursor, so that the silane coupling agent with a mercapto group is grafted to the surface of the vanadium dioxide precursor.
[0056] After obtaining the intermediate, according to the present invention, the silver source and the intermediate undergo a chelating reaction, and then, under the action of a strong reducing agent, a vanadium dioxide precursor modified by Ag element is obtained. Wherein, the silver source is selected from silver nitrate, and the silver nitrate is added in the form of a solution, and the concentration of the silver nitrate solution is 1 to 2.5 mol / L, preferably 1.5 to 2.0 mol / L; the strong reducing agent is selected from sodium borohydride; the molar ratio of the strong reducing agent to the silver ions in the silver source is 1:1 to 2:1, preferably 1:1 to 1.5:1. In this process, the silver source is added to the reaction system, and the surface of the vanadium dioxide precursor modified by the silane coupling agent with a mercapto group has a mercapto group, which chelates the silver ions and adsorbs the silver ions on the surface of the vanadium dioxide precursor particles. The subsequent addition of the strong reducing agent reduces the silver ions bridged on the surface of the vanadium dioxide precursor to silver element, and deposits on the surface of the vanadium dioxide precursor, thereby obtaining a vanadium dioxide precursor modified by Ag element.
[0057] In some embodiments of the present invention, a silane coupling agent with a mercapto group is preferably added to the suspension B, stirred at room temperature for 16 to 24 hours, so that the silane coupling agent with a mercapto group reacts with the hydroxyl groups on the surface of the vanadium dioxide precursor, and then a certain amount of silver source solution is added dropwise, and then a strong reducing agent is added to form a vanadium dioxide precursor-Ag (substance C). Among them, the mass fraction of the silane coupling agent with a mercapto group in the suspension B is 1% to 2%, preferably 1.2% to 1.5%; the concentration of the silver nitrate solution is 1 to 2.5 mol / L, preferably 1.5 to 2.0 mol / L, and its amount accounts for 0.5% to 1.5% of the mass of the suspension B, preferably 1.0% to 1.2%; the molar ratio of the reducing agent to the silver ion is 1:1 to 2:1. Then the vanadium dioxide precursor-Ag is filtered, washed, and dried to obtain a dry substance C.
[0058] Then, according to the present invention, the Ag-modified vanadium dioxide precursor, the solvent and the carbon nanotubes are mixed to obtain a vanadium dioxide precursor composite slurry.
[0059] Among them, the choice of solvent will directly affect the uniformity and stability of the dispersion of the Ag-modified vanadium dioxide precursor and the carbon nanotubes. Therefore, after screening, the present invention preferably selects the solvent as a mixed solution of ethylene glycol, glycerol and polyvinyl pyrrolidone, wherein the mass ratio of the polyvinyl pyrrolidone, ethylene glycol and glycerol is 1:10:10 to 1:4:4, preferably 1:8:8 to 1:3:3. The carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The present invention has no particular restrictions on the sources of the above-mentioned solvents and carbon nanotubes, and they can be general commercial products. In the present invention, the above-mentioned mixing is preferably carried out under stirring conditions, the mixing temperature is room temperature, specifically 10 to 30°C, preferably 15 to 25°C; the time is 0.7 to 3h, preferably 1.5 to 2h. In some preferred embodiments of the present invention, the mixing further includes an ultrasonic step.
[0060] In some specific embodiments of the present invention, substance C is preferably dispersed in ethylene glycol, glycerol, and polyvinyl pyrrolidone (PVP), wherein the mass ratio of polyvinyl pyrrolidone (PVP): ethylene glycol and glycerol is 1:10:10 to 1:4:4, substance C accounts for 8 to 20% of the total mass of the solution, preferably 10 to 15%, and stirred at room temperature for 0.2 to 1 hour, then single-walled or multi-walled carbon nanotubes are added and stirred for 0.5 to 1.5 hours, the concentration of the carbon nanotubes is 0.5 to 1 mol / L, and placed in an ultrasonic crusher for ultrasonication for 20 to 40 minutes, and the temperature is controlled below 40°C to obtain a vanadium dioxide precursor composite slurry D.
[0061] The total mass of the above solution is the total mass of the Ag-modified vanadium dioxide precursor, the solvent and the carbon nanotubes.
[0062] Finally, the vanadium dioxide precursor composite slurry is coated on the surface of the substrate and calcined to obtain a vanadium dioxide composite electrode material. The calcination temperature is 500-600°C, preferably 520-550°C; the time is 1-3 hours, preferably 1.5-2.5 hours; the calcination is preferably carried out in an inert atmosphere. The present invention has no particular limitation on the inert atmosphere, and the atmosphere can be any atmosphere familiar to those skilled in the art.
[0063] In some embodiments of the present invention, a copper sheet is used as a substrate, and a vanadium dioxide precursor composite slurry D is loaded on the surface of the substrate by an immersion pulling or coating method, and the thickness of the film formed on the surface is 50 to 200 μm, preferably 80 to 150 μm. Then, the substrate is placed in a vacuum tube furnace and heated to 500 to 600° C., kept warm for 1 to 3 hours, and argon gas is passed as a protective gas, and the gas flow rate is 1 to 3 L / min, preferably 1.5 to 2.5 L / min, to obtain a vanadium dioxide composite electrode material.
[0064] The preparation method of the vanadium dioxide composite electrode material provided by the present invention has high efficiency and strong controllability, mild reaction and simple operation, readily available raw materials and low experimental cost, is easy to implement, and is conducive to large-scale production.
[0065] The present invention also provides a vanadium dioxide composite electrode material prepared according to the above preparation method, which comprises a substrate and a vanadium dioxide composite film supported on the substrate. The vanadium dioxide composite film is constructed by VO2 deposited with Ag and carbon nanotubes; the substrate can be an alkali metal negative electrode material commonly used by technicians in the field, and can be specifically selected from copper sheets.
[0066] It should be pointed out that VO2-Ag has the quantum effect, small-scale effect and surface effect of nanomaterials, and also has the ability to move freely, penetrating power and super activity. At the same time, Ag, as a relatively cheap metal among precious metals, has unique electronic properties, optical properties, mechanical properties and catalytic properties, which can enhance the electronic conductivity of the electrode. The three-dimensional conductive network constructed by carbon nanotubes helps to overcome the dynamic constraints of the battery during the discharge process, so that the composite electrode material exhibits the best reversible capacity and good kinetic reaction, and can also effectively prevent the agglomeration of VO2-Ag particles, providing sufficient space for the expansion of the matrix during the lithiation process.
[0067] It should be noted that the above vanadium dioxide composite electrode material can be used as a negative electrode material of an alkali metal battery. Based on this, the present invention also provides a secondary battery, the negative electrode material of the secondary battery includes the above vanadium dioxide composite electrode material.
[0068] Exemplarily, the present invention provides a lithium-ion battery, which is assembled from a negative electrode sheet, a positive electrode sheet, an electrolyte and a shell in a glove box, and subjected to an electrochemical cycle test. The active material of the negative electrode sheet is a vanadium dioxide composite electrode material; the positive electrode sheet is a metal lithium sheet; the electrolyte is an LB-010 electrolyte produced by Suzhou Duoduo Chemical Technology Co., Ltd.; the diaphragm is a Celgard240 diaphragm, and the shell is a CR2025 button battery shell produced by Shenzhen Kejing.
[0069] The results showed that the lithium-ion battery has excellent lithium storage performance and high capacity retention rate.
[0070] In summary, the present invention can ensure that the prepared battery has excellent electrochemical performance, and ensure the coulombic efficiency and cycle life of the battery by spatially constructing and modifying the vanadium dioxide composite electrode material.
[0071] In order to further illustrate the present invention, the following examples are used to explain it in detail. The experimental raw materials used in the following examples of the present invention are generally commercially available products. The assembly method of the following battery can be carried out according to the method well known to those skilled in the art.
[0072] Example 1
[0073] Step 1:
[0074] A certain amount of vanadium leaching solution (main component sodium vanadium sulfate) is taken into a three-necked flask, wherein the vanadium concentration is 45 g / L, concentrated sulfuric acid is used to adjust the solution pH to 4, and after heating to a certain temperature of 90°C, a certain amount of oxalic acid is added, and the molar ratio of oxalic acid to vanadium ions is 1:1. After keeping warm for 2 hours, the color of the solution changes from orange-red to blue-black, forming solution A, and a certain amount of precipitant-urea is added to solution A, and the molar ratio of the precipitant to vanadium ions is 3:1. Then, it is heated to 100°C and stirred for 2 hours to form a suspension B with a precipitate (i.e., a vanadium dioxide precursor).
[0075] Step 2:
[0076] Add MPS coupling agent (3-mercaptopropyltriethoxysilane) to suspension B, stir at room temperature for 20 hours, make the silane coupling agent and the hydroxyl group on the surface of vanadium dioxide precursor undergo coupling reaction, then add a certain amount of silver nitrate solution dropwise, and then add strong reducing agent sodium borohydride to form vanadium dioxide precursor-Ag (substance C), wherein the coupling agent accounts for 1% of the mass fraction of suspension B, the concentration of silver nitrate solution is (1 mol / L), its amount accounts for 0.5% of the mass of suspension B, and the molar ratio of reducing agent to silver ion is 1:1. Then filter, wash and dry the precipitate (i.e., vanadium dioxide precursor-Ag) to obtain dry substance C.
[0077] Step 3:
[0078] Disperse substance C in ethylene glycol, glycerol and polyvinyl pyrrolidone (PVP), wherein the mass ratio of polyvinyl pyrrolidone (PVP): ethylene glycol and glycerol is (1:8:8), substance C accounts for 10% of the total mass of the solution, stir at room temperature for 0.5 h, then add multi-walled carbon nanotubes and continue stirring for 1 h, the concentration of carbon nanotubes is 0.5 mol / L, put into an ultrasonic crusher for ultrasonication for 30 min, and control the temperature below 40°C to obtain a vanadium dioxide precursor composite slurry D.
[0079] Step 4:
[0080] The copper sheet was used as the substrate, and the vanadium dioxide precursor composite slurry D was loaded on the substrate surface by coating method, and the surface film thickness was 100 μm. The substrate was placed in a vacuum tube furnace and heated to 550°C, kept warm for 1 hour, and argon was passed as the protective gas with a gas flow rate of 2 L / min to obtain a vanadium dioxide composite electrode material.
[0081] After returning to room temperature, it is assembled with the diaphragm, positive electrode plate, electrolyte and shell in the glove box. The active material of the negative electrode plate is a vanadium dioxide composite electrode material; the positive electrode plate is a metal lithium plate; the electrolyte is LB-010 electrolyte produced by Suzhou Duoduo Chemical Technology Co., Ltd.; the diaphragm is Celgard2400 diaphragm, and the shell is a CR2025 button battery shell produced by Shenzhen Kejing. A lithium-ion battery is obtained and an electrochemical cycle test is carried out.
[0082] Results: When the current density increases from 0.1, 0.2, 0.5, 1, 2 to 5A -1 When the reversible discharge capacity of the vanadium dioxide composite electrode material is 4213.2, 3931.8, 3516.7, 3137.7, 2880.1 and 2526.1 mAh g -1 When the current density returns to 0.1A again -1 When the vanadium dioxide composite electrode material is used, it still has a high capacity of 3901.8 mAh g -1 The lithium storage capacity is 200W, and the capacity retention rate of the charge specific capacity is as high as 95.1%, and the cross-sectional expansion rate is 30.2%.
[0083] Example 2
[0084] Step 1:
[0085] A certain amount of vanadium leaching solution (main component sodium vanadium sulfate) is taken into a three-necked flask, wherein the vanadium concentration is 40 g / L, concentrated sulfuric acid is used to adjust the solution pH to 3, and after heating to a certain temperature of 100°C, a certain amount of oxalic acid is added, and the molar ratio of oxalic acid to vanadium ions is 1:1. After keeping warm for 1 hour, the color of the solution changes from orange-red to blue-black, forming solution A, and a certain amount of precipitant sodium hydroxide is added to solution A, and the molar ratio of the precipitant to vanadium ions is 2:1. Then, it is heated to 100°C and stirred for 2 hours to form a suspension B with a precipitate (i.e., a vanadium dioxide precursor).
[0086] Step 2:
[0087] Add MPS coupling agent (3-mercaptopropyltriethoxysilane) to suspension B, stir at room temperature for 24 hours, make the silane coupling agent and the hydroxyl group on the surface of the vanadium dioxide precursor undergo coupling reaction, then drop a certain amount of silver nitrate solution, and then add a strong reducing agent sodium borohydride to form a vanadium dioxide precursor-Ag (substance C), wherein the coupling agent accounts for 1.5% of the mass fraction of suspension B, the concentration of silver nitrate solution is (1.5 mol / L), its amount accounts for 1% of the mass of suspension B, and the molar ratio of reducing agent to silver ion is 1:1. Then filter the precipitate (i.e., vanadium dioxide precursor-Ag), wash, and dry to obtain dry substance C.
[0088] Step 3:
[0089] Disperse substance C in ethylene glycol, glycerol and polyvinyl pyrrolidone (PVP), wherein the mass ratio of polyvinyl pyrrolidone (PVP): ethylene glycol and glycerol is (1:8:8), substance C accounts for 10% of the total volume of the solution, stir at room temperature for 0.5 h, then add multi-walled carbon nanotubes and continue stirring for 1 h, the concentration of carbon nanotubes is 0.5 mol / L, put into an ultrasonic crusher for 30 min, and control the temperature below 40°C to obtain a vanadium dioxide precursor composite slurry D.
[0090] Step 4:
[0091] The copper sheet is used as the substrate, and the vanadium dioxide precursor composite slurry D is loaded on the substrate surface by coating method, and the surface film thickness is 200μm. The substrate is placed in a vacuum tube furnace and heated to 600℃, kept warm for 1h, and argon is passed as the protective gas with a gas flow rate of 1L / min to obtain a vanadium dioxide composite electrode material. The schematic diagram is as follows Figure 1 shown.
[0092] Referring to Example 1, a lithium-ion battery was assembled and an electrochemical cycle test was performed.
[0093] Results: When the current density increases from 0.1, 0.2, 0.5, 1, 2 to 5A -1When the reversible discharge capacity of the vanadium dioxide composite electrode material is 4013.2, 3901.8, 3489.7, 3057.2, 2822.1 and 2416.2 mAh g -1 When the current density returns to 0.1A again -1 When the vanadium dioxide composite electrode material is still as high as 3821.8 mAh g -1 The lithium storage capacity is 200W, and the capacity retention rate of the charge specific capacity is as high as 94.2%, and the cross-sectional expansion rate is 33.1%.
[0094] Example 3
[0095] Step 1:
[0096] A certain amount of vanadium leaching solution (main component sodium vanadium sulfate) is taken into a three-necked flask, wherein the vanadium concentration is 50 g / L, concentrated sulfuric acid is used to adjust the solution pH to 4, and after heating to a certain temperature of 95°C, a certain amount of oxalic acid is added, and the molar ratio of oxalic acid to vanadium ions is 1:1. After keeping warm for 1 hour, the color of the solution changes from orange-red to blue-black, forming solution A, and a certain amount of precipitant ammonia water is added to solution A, and the molar ratio of the precipitant to vanadium ions is 5:1. Then, it is heated to 100°C and stirred for 2 hours to form a suspension B with a precipitate (i.e., a vanadium dioxide precursor).
[0097] Step 2:
[0098] Add MPS coupling agent (3-mercaptopropyltriethoxysilane) to suspension B, stir at room temperature for 18 hours, make the silane coupling agent and the hydroxyl group on the surface of the vanadium dioxide precursor undergo coupling reaction, then drop a certain amount of silver nitrate solution, and then add a strong reducing agent sodium borohydride to form a vanadium dioxide precursor-Ag (substance C), wherein the coupling agent accounts for 0.5% of the mass fraction of suspension B, the concentration of silver nitrate solution is (1 mol / L), its amount accounts for 1% of the mass of suspension B, and the molar ratio of reducing agent to silver ion is 1:1. Then filter the precipitate (i.e., vanadium dioxide precursor-Ag), wash, and dry to obtain dry substance C.
[0099] Step 3:
[0100] Disperse substance C in ethylene glycol, glycerol and polyvinyl pyrrolidone (PVP), wherein the mass ratio of polyvinyl pyrrolidone (PVP): ethylene glycol and glycerol is (1:10:10), substance C accounts for 10% of the total volume of the solution, stir at room temperature for 1 hour, then add multi-walled carbon nanotubes and continue stirring for 0.5 hour, the concentration of carbon nanotubes is 0.5 mol / L, put into an ultrasonic crusher for ultrasonication for 20 minutes, and control the temperature below 40°C to obtain a vanadium dioxide precursor composite slurry D.
[0101] Step 4:
[0102] The copper sheet was used as the substrate, and the vanadium dioxide precursor composite slurry D was loaded on the substrate surface by coating method, and the surface film thickness was 50 μm. The substrate was placed in a vacuum tube furnace and heated to 500°C, kept warm for 2 hours, and argon was passed as the protective gas with a gas flow rate of 2L / min to obtain a vanadium dioxide composite electrode material.
[0103] Referring to Example 1, a lithium-ion battery was assembled and an electrochemical cycle test was performed.
[0104] Results: When the current density increases from 0.1, 0.2, 0.5, 1, 2 to 5A -1 When the reversible discharge capacity of the vanadium dioxide composite electrode material is 3920.2, 3821.1, 3422.6, 3013.4, 2814.2 and 2401.1 mAh g -1 When the current density returns to 0.1A again -1 When the vanadium dioxide composite electrode material is used, it still has a high capacity of 3802.6 mAh g -1 The lithium storage capacity is 200W, and the capacity retention rate of the charge specific capacity is as high as 95.1%, and the cross-sectional expansion rate is 31.8%.
[0105] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a vanadium dioxide composite electrode material, characterized in that: The following steps are involved: (1) reacting the vanadium leaching solution with a reducing agent at a pH of 2 to 6, mixing the obtained tetravalent vanadium solution with a precipitant and causing a precipitation reaction to obtain a vanadium dioxide precursor suspension; (2) mixing a silane coupling agent with a mercapto group with a vanadium dioxide precursor suspension and reacting the mixture to obtain an intermediate; subjecting the silver source to a chelating reaction with the intermediate and, under the action of a strong reducing agent, obtaining a vanadium dioxide precursor modified with Ag; (3) mixing a vanadium dioxide precursor modified with Ag, a solvent and carbon nanotubes to obtain a vanadium dioxide precursor composite slurry; (4) coating the vanadium dioxide precursor composite slurry on the surface of the substrate and calcining it to obtain a vanadium dioxide composite electrode material.
2. The preparation method according to claim 1, characterized in that: The reducing agent is selected from oxalic acid; The molar ratio of the reducing agent to the vanadium ions in the vanadium leaching solution is 1:(1-2); The precipitant is selected from any one or more of urea, ammonia water or sodium hydroxide; The molar ratio of the precipitant to the vanadium ions in the vanadium leaching solution is (2-10):1; The pH is 2-6 and is regulated by concentrated sulfuric acid.
3. The preparation method according to claim 1 or 2, characterized in that: The reaction temperature in step (1) is 80-100° C. and the reaction time is 1.0-3.0 h; The precipitation reaction is carried out at a temperature of 95 to 100° C. and for a time of 1.0 to 5.0 h.
4. The preparation method according to any one of claims 1 to 3, characterized in that The silane coupling agent with a mercapto group is 3-mercaptopropyltriethoxysilane; The silane coupling agent with mercapto groups accounts for 1-2% of the mass of the vanadium dioxide precursor suspension; The silver source is selected from silver nitrate; the silver nitrate is added in the form of a solution, the concentration of the silver nitrate solution is 1-2.5 mol / L, and the mass of the silver source accounts for 0.5-1.5% of the mass of the vanadium dioxide precursor suspension; The strong reducing agent is selected from sodium borohydride; The molar ratio of the strong reducing agent to the silver ions in the silver source is 1:1 to 2:1; The reaction temperature of the silane coupling agent with mercapto group and the vanadium dioxide precursor suspension is 10-30° C. and the reaction time is 16-24 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The solvent is selected from ethylene glycol, glycerol and polyvinyl pyrrolidone; The mass ratio of polyvinyl pyrrolidone, ethylene glycol and glycerol is 1:10:10 to 1:4:4; The carbon nanotubes are selected from single-walled carbon nanotubes and / or multi-walled carbon nanotubes; The substrate is selected from copper sheets.
6. The preparation method according to any one of claims 1 to 5, characterized in that The vanadium dioxide precursor deposited with the Ag elemental modification accounts for 8-20% of the total mass of the solution; the total mass of the solution is the total mass of the vanadium dioxide precursor modified with the Ag elemental modification, the solvent and the carbon nanotubes; The concentration of the carbon nanotubes is 0.5-1 mol / L.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixing temperature in step (3) is 10-30°C and the time is 0.7-3h; the mixing further includes an ultrasonic step; The calcination temperature is 500-600°C and the calcination time is 1-3h; The calcination is performed in an inert atmosphere.
8. A vanadium dioxide composite electrode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The vanadium dioxide composite electrode material comprises a substrate and a vanadium dioxide composite film supported on the substrate; The vanadium dioxide composite film is constructed by VO2 deposited with Ag single substance and carbon nanotubes.
9. The vanadium dioxide composite electrode material according to claim 8, characterized in that: The thickness of the vanadium dioxide composite film is 50-200 μm.
10. A secondary battery, characterized in that: The negative electrode material of the secondary battery comprises a vanadium dioxide composite electrode material prepared by the preparation method according to any one of claims 1 to 7 or a vanadium dioxide composite electrode material according to claim 8 or 9; The secondary battery includes a lithium ion battery or a sodium ion battery.
Citation Information
Cited By
High-conductivity vanadium redox flow battery electrolyte and preparation method thereof
CN121035280A
Preparation method of chromium-doped VO2 precursor
CN121896452A